Recruitment and plasticity in diaphragm, intercostal, and abdominal muscles in unanesthetized rats - Navarrete-Opazo, A. (American Physiological Society, 2014)
Although rats are a frequent model for studies of plasticity in respiratory motor control, the relative capacity of rat accessory respiratory muscles to express plasticity is not well known, particularly in unanesthetized animals. Here, we characterized external intercostal (T2, T4, T5, T6, T7, T8, T9 EIC) and abdominal muscle (external oblique and rectus abdominis) electromyogram (EMG) activity in unanesthetized rats via radiotelemetry during normoxia (Nx: 21% O(2)) and following acute intermittent hypoxia (AIH: 10 × 5-min, 10.5% O(2); 5-min intervals). Diaphragm and T2–T5 EIC EMG activity, and ventilation were also assessed during maximal chemoreceptor stimulation (MCS: 7% CO(2), 10.5% O(2)) and sustained hypoxia (SH: 10.5% O(2)). In Nx, T2 EIC exhibits prominent inspiratory activity, whereas T4, T5, T6, and T7 EIC inspiratory activity decreases in a caudal direction. T8 and T9 EIC and abdominal muscles show only tonic or sporadic activity, without consistent respiratory activity. MCS increases diaphragm and T2 EIC EMG amplitude and tidal volume more than SH (0.94 ± 0.10 vs. 0.68 ± 0.05 ml/100 g; P < 0.001). Following AIH, T2 EIC EMG amplitude remained above baseline for more than 60 min post-AIH (i.e., EIC long-term facilitation, LTF), and was greater than diaphragm LTF (41.5 ± 1.3% vs. 19.1 ± 2.0% baseline; P < 0.001). We conclude that 1) diaphragm and rostral T2–T5 EIC muscles exhibit inspiratory activity during Nx; 2) MCS elicits greater ventilatory, diaphragm, and rostral T2–T5 EIC muscle activity vs. SH; and 3) AIH induces greater rostral EIC LTF than diaphragm LTF.